2020
DOI: 10.1002/anie.202007439
|View full text |Cite
|
Sign up to set email alerts
|

An α‐Cyclopropanation of Carbonyl Derivatives by Oxidative Umpolung

Abstract: The reactivity of iodine(III) reagents towards nucleophiles is often associated with umpolung and cationic mechanisms. Herein, we report a general process converting a range of ketone derivatives into α‐cyclopropanated ketones by oxidative umpolung. Mechanistic investigation and careful characterization of side products revealed that the reaction follows an unexpected pathway and suggests the intermediacy of non‐classical carbocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…[11b] Replacing the aryl group in 11 with an olefin as in 14, led to a cyclopropanation product 15, along with an unexpected 1,2-substituted cyclobutane 16 both as single respective trans diastereomers. [12] From the isotope ( 2 H and 13 C) scrambling, the authors concluded that both 15 and 16 are formed from non-classical carbocations as represented by the selected resonance structures drawn. A range of cyclopropane products 15 (19 examples, 53-94 % yield) could be synthesized by this method.…”
Section: Hypervalent Iodonium Chemistrymentioning
confidence: 99%
“…[11b] Replacing the aryl group in 11 with an olefin as in 14, led to a cyclopropanation product 15, along with an unexpected 1,2-substituted cyclobutane 16 both as single respective trans diastereomers. [12] From the isotope ( 2 H and 13 C) scrambling, the authors concluded that both 15 and 16 are formed from non-classical carbocations as represented by the selected resonance structures drawn. A range of cyclopropane products 15 (19 examples, 53-94 % yield) could be synthesized by this method.…”
Section: Hypervalent Iodonium Chemistrymentioning
confidence: 99%
“…Encouraged by our previous work on I(III)-mediated rearrangements, 11,12 on enolonium species 8, would undergo elimination to form 7.…”
mentioning
confidence: 99%
“…It is additionally worth mentioning that during the examination of the conditions employing PIDA as the I(III) reagent, we observed the formation of distinct side products (α-and β-acetates), generated by competitive reactions with intermediates 8 and 9. 11,12,15 Attempting to avoid the formation of these byproducts, we increased the amount of the activator TMSOTf, which led to an improved isolated yield (82%) of the αarylated enone 7a (entry 8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The preformation of the enol species as a silyl enol ether or Ir enolate 3 proved to be an elegant solution to this limitation and opened the door for applying external nucleophiles if linear iodane reagents 4 are used. α-Aminations, [12] cyanations, [13] azidations, [14] (hetero)arylation, [15] and cyclopropanation [16] of pre-modified ketones have thus become available (scheme 1b). Despite this tremendous progress, specific enol/enolate formation, no matter whether in-situ or beforehand, constitutes still a limiting factor, as regiocontrol is difficult to achieve if more than one enolisable C atoms are present.…”
mentioning
confidence: 99%